Aromaterapi Lemon untuk Mengurangi Mual dan Muntah pada Ibu Hamil: Lemon Aromatherapy to Reduce Nausea and Vomiting in Pregnancy - Widayati; Windayanti, Hapsari; Hapitha (Indonesian Journal of Midwifery (IJM), 2024)
The first trimester of pregnancy is when the embryo or fetus is 0–14 weeks old in the body. Nausea and vomiting are natural and common symptoms that occur in the first trimester of pregnancy, often between the 6th and 10th weeks of pregnancy. Nausea usually occurs in the morning, but can also occur at any time, even at night. Lemon aromatherapy contains ingredients that can kill meningococcus and typhoid bacteria, has an antifungal effect, effectively neutralizes unpleasant odors, has anti-anxiety, depressant and stress-relieving effects, and improves and focuses the mind. To find out the differences in nausea and vomiting before and after giving lemon aromatherapy to pregnant women. The research is quantitative research using the Quasi Experiment method with a one group pre-test and post-test design without a control group. The sample used a total sampling of 16 trimester pregnant women. To determine differences in this study, the Wilcoxon test was used because the data was not normally distributed. Testing the normality of the data using the Shapiro-Wilk test showed that the results were not normally distributed. The results of statistical tests using the Wilcoxon test obtained a p value = 0.000 or smaller than the α value (0.05). It was concluded that Ho was rejected, meaning there was a difference in nausea and vomiting between before and after being given lemon aromatepai to pregnant women. Lemon aromatherapy can be used as a treatment that can be used to help reduce nausea and vomiting in pregnant women..   Abstrak Kehamilan trimester pertama adalah kondisi embrio atau janin berada pada usia 0–14 minggu di dalam tubuh. Mual dan muntah merupakan gejala alami dan umum yang terjadi pada trimester pertama kehamilan seringnya pada usia kehamilan antara minggu ke-6 dan ke-10. Mual biasanya terjadi pada pagi hari, namun dapat juga terjadi kapan saja bahkan pada malam hari. Aromaterapi lemon mengandung bahan yang dapat membunuh bakteri meningokokus dan tifus, memiliki efek antijamur, efektif menetralkan bau tak sedap, memiliki efek anticemas, depresan dan penghilang stres, serta meningkatkan dan memfokuskan pikiran. Untuk mengetahui perbedaan mual muntal sebelum dan sesudah pemberian aromaterapi lemon pada ibu hamil. Penelitian merupakan penelitain kuantitaf dengan metode Quasi Experiment dengan rancangan one group pre-test and post-test design tanpa kelompok kontrol. Sampel menggunakan total sampling sebanyak 16 ibu hamil trimester, Untuk mengetahui perbedaan pada penelitian ini menggunakan Uji wilcoxon dikarenakan data berdistribusi tidak normal. Uji normalitas data dengan uji Shapiro-Wilk didapatkan bahwa hasilnya tidak berdistribusi normal. Hasil uji statistik yang menggunakan uji wilcoxon didapatkan nilai p = 0,000 atau lebih kecil dari nilai α (0,05). Disimpulkan bahwa Ho ditolak artinya terdapat perbedaan mual muntah antara sebelum dengan sesudah diberikan aromatepai lemon pada ibu hamil. Aromaterapi lemon  dapat digunakan sebagai salah satu asuhan yang dapat digunakan untuk membantu menurunkan mua muntah pada ibu hamil.